Bilateral agreement for the academic year 2011-2013 LLP Programme: higher education Erasmus between Aristotle University of Thessaloniki and Universidade Lusíada de Lisboa - Universidade Lusíada de Lisboa (2016)
- Cooperate in the activities within the LLP programme; - Erasmus subject area: Architecture.